Rancang Bangun Smart System Pendeteksi Air Layak Minum Pada Sumur di Daerah Pesisir Pantai Berbasis Internet Of Things (IoT) - Imam Fathurrahman; Indra Gunawan; LM Samsu; Nia Budiarti (Infotek: Jurnal Informatika dan Teknologi, 2023)
Water is an important natural resource for human life, but in some coastal areas, the availability of clean water is often a serious problem. One source of water used by communities in these areas is wells, which often do not meet health standards for consumption. Manual methods for detecting well water quality still require long, expensive, and inefficient processes. Therefore, the development of a system that can detect water quality in real-time and provide fast and accurate information to the community is needed. The Internet of Things (IoT) technology, which allows objects to be connected to the internet, provides a solution that can be utilized. In this study, a Smart System was designed using salinity and manganese sensors to monitor the real-time quality of well water in coastal areas. Data from these sensors are sent to a server through the internet and analyzed to provide information to users via the Blynk application on their smartphones. With this system, communities can directly monitor the quality of well water, take appropriate actions, and safeguard the health of local residents. Additionally, this system can also assist relevant government or institutions in monitoring and taking quick actions in response to changes in well water quality in coastal areas